2008
DOI: 10.1016/j.ccr.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of C/EBPα Mutant Acute Myeloid Leukemia Reveals a Common Expression Signature of Committed Myeloid Leukemia-Initiating Cells

Abstract: Mutations in the CEBPA gene are present in 7%-10% of human patients with acute myeloid leukemia (AML). However, no genetic models exist that demonstrate their etiological relevance. To mimic the most common mutations affecting CEBPA-that is, those leading to loss of the 42 kDa C/EBPalpha isoform (p42) while retaining the 30kDa isoform (p30)-we modified the mouse Cebpa locus to express only p30. p30 supported the formation of granulocyte-macrophage progenitors. However, p42 was required for control of myeloid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
244
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(272 citation statements)
references
References 38 publications
20
244
1
3
Order By: Relevance
“…17,20 However, previous studies did not find leukemic potential in mice carrying monoallelic Cebpa L/ þ or Cebpa K/ þ mutations. 11,18 On the other hand, it has been shown that FLT3 ITD can phosphorylate C/EBPa, which could lead to a loss of function in the absence of other mutations explaining why some AML only carry a monoallelic C/EBPa mutation. 21,22 In addition, recent work using retroviral overexpression demonstrated that a C-terminal Cebpa mutation (C/EBPa-C m ) was sufficient to cause AML and that FLT3 ITD could shorten the latency of AML induced by C/EBPa-C m .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,20 However, previous studies did not find leukemic potential in mice carrying monoallelic Cebpa L/ þ or Cebpa K/ þ mutations. 11,18 On the other hand, it has been shown that FLT3 ITD can phosphorylate C/EBPa, which could lead to a loss of function in the absence of other mutations explaining why some AML only carry a monoallelic C/EBPa mutation. 21,22 In addition, recent work using retroviral overexpression demonstrated that a C-terminal Cebpa mutation (C/EBPa-C m ) was sufficient to cause AML and that FLT3 ITD could shorten the latency of AML induced by C/EBPa-C m .…”
Section: Resultsmentioning
confidence: 99%
“…11,14,18 Briefly, insertion of a premature stop codon between the p42 and p30 C/EBPa start sites results in exclusive p30 C/EBPa translation (Cebpa Lp30 or L allele; Cebpa L/ þ ). The K313KK mutation was generated by insertion of an additional lysine in the C/EBPa coding sequence (Cebpa K313KK or K allele; Cebpa K/ þ ) leading to disruption of the basic region leucine zipper of C/EBPa.…”
Section: Mouse Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of N-and C-terminal mutations have distinct features that result in leukaemia development (23,24). Murine knockin studies investigating p30 oncogenicity in the absence of C/EBPα p42 showed that p30 induced fully penetrant transplantable AML (25). p30 is sufficient for haematopoietic commitment to the myeloid lineage, it enables transition from the common myeloid progenitor (CMP) to the GMP stage.…”
Section: Introductionmentioning
confidence: 99%
“…p30 is sufficient for haematopoietic commitment to the myeloid lineage, it enables transition from the common myeloid progenitor (CMP) to the GMP stage. However it does not retain the ability to control proliferation and myeloid progenitors have greatly increased self renewal capacities (25).…”
Section: Introductionmentioning
confidence: 99%